Complete genome sequences of Francisella noatunensis subsp. orientalis strains FNO12, FNO24 and FNO190: a fish pathogen with genomic clonal behavior. Issue 1 (December 2016) - Gonçalves, Lucas; de Castro Soares, Siomar; Pereira, Felipe; Dorella, Fernanda; de Carvalho, Alex; de Freitas Almeida, Gabriel; Leal, Carlos; Azevedo, Vasco; Figueiredo, Henrique
Abstract The genusFrancisella is composed of Gram-negative, pleomorphic, strictly aerobic and non-motile bacteria, which are capable of infecting a variety of terrestrial and aquatic animals, among whichFrancisella noatunensis subsp.orientalis stands out as the causative agent of pyogranulomatous and granulomatous infections in fish. Accordingly, F. noatunensis subsp. orientalis is responsible for high mortality rates in freshwater fish, especially Nile Tilapia. In the current study, we present the genome sequences ofF. noatunensis subsp.orientalis strains FNO12, FNO24 and FNO190. The genomes include one circular chromosome of 1, 859, 720 bp, consisting of 32 % GC content, 1538 coded proteins and 363 pseudogenes for FNO12; one circular chromosome of 1, 862, 322 bp, consisting of 32 % GC content, 1537 coded proteins and 365 pseudogenes for FNO24; and one circular chromosome of 1, 859, 595 bp, consisting of 32 % GC content, 1539 coded proteins and 362 pseudogenes for FNO190. All genomes have similar genetic content, implicating a clonal-like behavior for this species.